2015
DOI: 10.1097/qad.0000000000000692
|View full text |Cite
|
Sign up to set email alerts
|

Association between gp120 envelope V1V2 and V4V5 variable loop profiles in a defined HIV-1 transmission cluster

Abstract: Our observations are consistent with a structural association between the V1V2 and V4V5 gp120 regions that is lost following viral transmission. These structural considerations should be taken into consideration when devising HIV-1 immunogens aimed at inducing protective antibody responses targeting transmitted viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…This increase in the V1-V2 length and PNGs has also been detected thorough chronic infections from early to late viral Env sampling like in our work (49). Likewise in a group of individuals infected with closely related viruses higher PNGs density has been observed in the V1-V5 region of the gp120 during chronic infection compared to those oberved during the early acute infection phase (82). In viruses from the HIV-1 subtype B, it seems that early after viral transmission to a new host a selection for viral variants with shorter variable regions and a reduced degree of PNGs occurs (83).…”
Section: Discussionmentioning
confidence: 98%
“…This increase in the V1-V2 length and PNGs has also been detected thorough chronic infections from early to late viral Env sampling like in our work (49). Likewise in a group of individuals infected with closely related viruses higher PNGs density has been observed in the V1-V5 region of the gp120 during chronic infection compared to those oberved during the early acute infection phase (82). In viruses from the HIV-1 subtype B, it seems that early after viral transmission to a new host a selection for viral variants with shorter variable regions and a reduced degree of PNGs occurs (83).…”
Section: Discussionmentioning
confidence: 98%
“…Little is known about V4; however, V4 is thought to be critical for Env entry into specific HIV strains (Li et al, 2014), and recent studies using both sequences from the HIV database and transmission clusters have found a negative correlation between the V1V2 and V4V5 regions in terms of amino acid lengths during transmission. Notably, this correlation was lost following seroconversion (Pollakis et al, 2015), indicating that the relationship between these regions may be complex. Based on our current findings, V4 may also play an important role in transmission.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still considerable debate about Env properties of TF HIV-1. A reduced glycan shield on TF HIV-1 (9,19,20) was thought to improve replicative fitness and/or host cell entry, i.e. possibly a favorable trait for transmission.…”
Section: Downloaded Frommentioning
confidence: 99%
“…However, there is still considerable debate about Env properties of TF HIV-1. A reduced glycan shield on TF HIV-1 ( 9 , 19 , 20 ) was thought to improve replicative fitness and/or host cell entry; i.e., it may be a favorable trait for transmission. However, TF clones with fewer N-linked glycan sites had no clear advantage in terms of replicative rate, receptor/coreceptor binding, or entry efficiency over HIV-1 found during chronic disease ( 11 , 12 , 21 ).…”
Section: Introductionmentioning
confidence: 99%